2023
DOI: 10.1371/journal.pone.0283341
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of soil microorganisms in different complex soil layers in Mu Us sandy land

Abstract: The soft rock in Mu Us Sandy Land has rich resources and high content of clay minerals. The combination of soft rock with sand can play a certain role in sand fixation and promote the green development of ecological environment. In this paper, the aeolian sandy soil in Mu Us Sandy was taken as the research object, and it was mixed with soft rock to form composite soil. The four volume ratios of soft rock to sand were respectively 0:1, 1:5, 1:2 and 1:1. And CK, P1, P2 and P3 were used to represent the above fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
(34 reference statements)
0
1
0
Order By: Relevance
“…Moreover, we found that the Shannon index plays a crucial role in rice yield, as it displayed a significant positive effect on rice yield (figure 5). Previous studies have suggested that organic fertilization greatly affects soil microbiota structure and their activities in nutrient cycling [31,32] and can adjust soil microbial composition and enhance soil enzyme activity [33]. In this study, the abundance of the bacterial phylum Chloroflexi increased under organic fertilization, while the alpha diversity, indicated by Chao1, ACE, and Shannon indices, decreased.…”
Section: Discussionmentioning
confidence: 51%
“…Moreover, we found that the Shannon index plays a crucial role in rice yield, as it displayed a significant positive effect on rice yield (figure 5). Previous studies have suggested that organic fertilization greatly affects soil microbiota structure and their activities in nutrient cycling [31,32] and can adjust soil microbial composition and enhance soil enzyme activity [33]. In this study, the abundance of the bacterial phylum Chloroflexi increased under organic fertilization, while the alpha diversity, indicated by Chao1, ACE, and Shannon indices, decreased.…”
Section: Discussionmentioning
confidence: 51%